PENGARUH DOSIS PUPUK UREA TERHADAP TINGGI TANAMAN DAN PRODUKSI SEGAR RUMPUT ODOT (Pennisetum purpureum cv.Mott) - Eryanto Didit; Susilo Rahardjo; Fany Dwi Evadewi; Tri Sukmaningsih (MEDIA PETERNAKAN, 2024)
Forage is one of the things that determines the success of a livestock business, so it is necessary to have forage that is good in quality and quantity. Therefore, the problem raised in this research is the productivity of odot grass (Pennisetum purpureum cv. Mott) which was given urea fertilizer at different doses, at the age of first cutting. Because feed is very important for livestock development, feed must be sufficient for livestock growth and survival. Forage is the main source of feed for ruminant animals, a ratio of 40:60 is optimal for dry matter or pasture concentrate to feed or fortifier concentrate. This research used a Completely Randomized Design (CRD) with five treatments and four replications. Treatments P0, P1, P2, P3, and P4 are as follows: Treatment P0 odot grass (control) + urea + 10 gr/m2, Treatment P2 odot grass + urea + 10 gr/m2, Treatment P3 odot grass + urea + 30 gr/m2, and Treatment P4 odot grass + 40 gr/m2 urea.